The mutual relationship between euthanasia and preservation of life from the Islamic jurisprudence perspective - Abdoljabari, Morteza; Fani, Mahdi; Ghoreishi, Seyyed Majid; Rajabzadeh , Ali; Karamkhani, Marzieh (Researcher Bulletin of Medical Sciences, 2020)
Introduction: All divine religions have paid a special attention to the preservation of life. In a similar vein, the last monotheistic religion, Islam, has emphasized the need to respect this right and the need to preserve human life. Some solutions have always been proposed on the need to respect and exercise this right. All divine religions are against euthanasia and the views of its opponents and euthanasia has been interdicted in many verses in the Quran. The current study was an attempt to demonstrate the importance of preservation of life from the perspective of Islam and to examine this issue from a religious point of view and the emphasis on the need to preserve human life Materials and Methods: The study adopted a descriptive-analytical design. In line with this design, various books on Islamic sciences, interpretation, narrations, and jurisprudence were consulted. Furthermore, using the databases, related papers were also consulted. Results: According to Islam, God is the genuine owner of human bodies and lives. Humans cannot jeopardize their lives and perform euthanasia without a legitimate reason based on jurisprudence or wisdom but should use their life in line with the goal of creation, i.e., to serve God. The importance of preservation of life is primarily recognized by wisdom1. The Holy Quran and Islamic narrations have also recognized the need to preserve human life. Islamic scientists (clergymen) have also emphasized its obligation. Conclusion: Human beings are obliged to avert dangers and do their best to preserve their lives. Every action, which may lead to euthanasia, is against wisdom Islamic jurisprudence